Resource conservation technologies for sustainable development of agriculture: A case study in Indian Punjab - J M Singh; Jatinder Sachdeva; Prem Chand; Jasdev Singh; Baljinder Kaur (Agricultural Economics Research Review, 2023)
Punjab has remained pioneer in adopting new farm technologies ever since the advent of paddy and wheat based Green Revolution. However, over time, the emergence of monoculture of paddy and wheat in their respective growing seasons has caused ecological and environmental problems, which needs to be addressed for sustainable development of agriculture. This study has developed optimal crop plans for Punjab, and evolved scenarios considering potential resource conservation technologies options. Results reveal that continuous of existing policies is unlikely to reduce paddy-wheat mono-cropping. The adoption of resource conservation technologies, viz. sowing wheat with Happy Seeder, and direct seeding of paddy and its short-duration have the potential to save water and without any yield or income penalty. Incentivizing farmers for adoption of resource conservation technologies can divert paddy area to crops grown with less water.